Preoperative and postoperative medical therapies for chronic rhinosinusitis: National surveys among Chinese otolaryngologists - Zhen-Xiao Huang (KeAi Communications Co., Ltd., 2018)
Objective: The aim of this study was to evaluate clinical practice patterns of preoperative and postoperative medical therapies immediately surrounding sinus surgery for chronic rhinosinusitis (CRS) by Chinese otolaryngologists. Methods: Two anonymous web-based surveys of preoperative and postoperative medical therapies were performed. These surveys assessed the frequency of prescription of oral corticosteroids, intranasal corticosteroid sprays, oral antibiotics, nasal saline irrigation, oral antihistamines, nasal antihistamines, anti-leukotriene agents, topical decongestants and oral mucolytics. Results: A total of 304 (17.5%) preoperative and 143 (23.5%) postoperative questionnaires were completed and returned. Seventy-eight percent, 63% and 56% of respondents used preoperative intranasal corticosteroid sprays, oral antibiotics and oral mucolytics “always or often”, respectively. Ninety-four percent, 93%, 72% and 69% of respondents used postoperative intranasal corticosteroid sprays, nasal saline irrigation, oral antibiotics and oral mucolytics “always or often”, respectively. Oral antihistamines, nasal antihistamines, anti-leukotrienes and topical decongestants were not commonly used preoperatively or postoperatively. Conclusions: Our study demonstrated that current practice patterns of preoperative medical therapies among otolaryngologists are not uniformly based on evidence-based outcomes research. Postoperative oral antibiotics, intranasal corticosteroid sprays, nasal saline irrigation and oral mucolytics are commonly used by a majority of Chinese otolaryngologist for CRS. Practice patterns of postoperative medical therapy reflect recent guidelines. Keywords: Chronic rhinosinusitis, Preoperative, Postoperative, Medical therapy, Survey